The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.4236/oalib.1103987
|View full text |Cite
|
Sign up to set email alerts
|

Total Phenolic and Flavonoid Content and Antioxidant Activities of Ten Malaysian Wild Mushrooms

Abstract: Mushrooms have been studied and found to accumulate a variety of secondary metabolites with antioxidant activities such as phenolic compounds. Besides phenolics, other bioactive components such as flavanoids from mushrooms are also generally associated with antioxidant activities. Previous studies have reported the association of mushrooms with their antioxidant potentials. However, very few studies are related to unexplored Malaysian wild mushrooms as a new potential source of antioxidant for which to best of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 13 publications
1
8
1
Order By: Relevance
“…Also, a higher FRAP value was observed with mushroom samples exposed to sunlight (Table 3). These obtained values are higher than those found by Azieana et al [42] who reported that the total phenolic content of fresh mushroom was 0.024 mg GAE/g. [43], while protein and ash values were higher.…”
Section: Chemical Composition Bioactive Compounds Andcontrasting
confidence: 80%
“…Also, a higher FRAP value was observed with mushroom samples exposed to sunlight (Table 3). These obtained values are higher than those found by Azieana et al [42] who reported that the total phenolic content of fresh mushroom was 0.024 mg GAE/g. [43], while protein and ash values were higher.…”
Section: Chemical Composition Bioactive Compounds Andcontrasting
confidence: 80%
“…Total flavonoid content was determined following the method by Singh et al (2012) and Jinting et al (2017) [21,22]. Accurately, 1 mL of sample or standard was diluted with 4 mL distilled water and 0.3 mL of 5% sodium nitrate solution was added.…”
Section: Determination Of Total Flavonoid Contentmentioning
confidence: 99%
“…Species from subcluster 1B presented low values of TPC but better values of DPPH suggesting the contribution of other compounds to its antioxidant capacity. On the other hand, seven lichens species (Cetraria commixta, Cetraria nivalis, Cetraria cucullata, Cetraria crespoae, Cetraria ericetorum, Tuckneraria ahtii, and Nephromopsis pallescens) composed cluster 2. e cluster 2 included lichen species, mostly consisted of Cetraria species, characterized by the lowest antioxidant properties and the lowest phenolic content values [31,39,40]. Cluster 3 is composed of a single species Dactylina arctica.…”
Section: Resultsmentioning
confidence: 99%